The changing structure of the maize seed industry in Zambia: prospects for orange maize - Smale, Melinda; Simpungwe, Eliab; Birol, Ekin; Kassie, Girma T.; Groot, Hugo de; Mutale, Raphael (Wiley, 2015)
Zambia's maize seed industry is currently one of the strongest and most competitive in Sub‐Saharan Africa. This paper describes the changing structure of the maize seed industry and seed supply chain in Zambia. The aim of the paper is to propose elements of a marketing strategy for seed production and delivery of recently released, provitamin A‐rich, orange maize varieties. Information sources include a thorough review of the literature, a statistical survey of farmers in the major maize‐producing areas of the country, and key informant interviews conducted with seed company representatives. We discuss the merits of two strategies: (1) liberalizing the provision of original orange maize planting material to all seed companies with the aim of maximizing the impact of this public health intervention, and (2) exclusive rights granted to companies with the goals of preserving differentiated products and ensuring standard seed quality to protect the brand. We find that, exclusive or not, risk‐sharing contracts with any company that takes up this product, as well as building and maintaining a unique brand for orange maize would be essential for the success of this product.